Analisis Kekerasan Permukaan Titanium-6A1-4V Pada Proses EDM Sinking Dengan Aplikasi Response Surdace Methodology (RSM) - Yuliyanto Yuliyanto (Manutech : Jurnal Teknologi Manufaktur, 2017)
This study looked at the effect of severed EDM process parameters on the optimum value of titanium alloy hardness. this study uses Design Expert 9.0 software to help develop an experimental plan of response surface method models and CCD. The machine used is Hitachi Electrical Discharge Machining (EDM) brand with Series H-DS02-S. Material used titanium 6Al-4V. Electrode used copper (Cu). The process parameters used are Current (A), On time (?s) and Off time (?s). Coolant fluid using Hydroseal 63H. The results of data processing there are 20 experiments. This research shows optimum machining condition for hardness (HV) is 322. Analysis of variance (Anova) shows the value of F arithmetic is 3,94, MSE is 0,022 and p (0,0794). The increase of current and on-time values ??gives a great influence on surface roughness. The increase of Off time value does not give significant effect to the roughness. The next research will be done with 5 (five) process parameters, Current, On time, Off time, Machining Voltage and Servo feed.